Comprehensive Phenotypic Characterization and Genomic Analysis Unveil the Probiotic Potential of Bacillus velezensis K12 - Tang, Yingying; Li, Tian; Huang, Yihong; Wu, Liangliang; Liu, Xiaobo; Yue, Ruichao; Yuan, Jianmin (Animals (Basel), 2025)
Bacillus spp. have emerged as pivotal sources of probiotic preparations, garnering considerable attention in recent years owing to their vigorous bacteriostatic activity and antimicrobial resistance. This study aimed to investigate these probiotic characteristics in depth and verify the safety of Bacillus velezensis K12, a strain isolated from broiler intestine. The K12 strain was identified as Bacillus velezensis based on its morphology and 16S rDNA sequence homology analysis. Subsequently, B. velezensis K12 was evaluated for acid resistance, bile salt resistance, gastrointestinal tolerance, drug sensitivity, and antimicrobial activity. Additionally, whole-genome sequencing technology was employed to dissect its genomic components further, aiming to explore its potential applications as a probiotic strain. B. velezensis K12 was sensitive to six antibiotics and had acid tolerance. Furthermore, it showed potent antimicrobial activity against a wide range of pathogenic bacteria, including Escherichia coli (E. coli), Staphylococcus aureus, Salmonella, Clostridium perfringens, Bacillus cereus, and Vibrio parahaemolyticus. The complete genome sequencing of B. velezensis K12 revealed a genomic length of 3,973,105 base pairs containing 4123 coding genes, among which 3973 genes were functionally annotated. The genomic analysis identified genes associated with acid and bile tolerance, adhesion, antioxidants, and secondary metabolite production, whereas no functional genes related to enterotoxins or transferable antibiotic resistance were detected, thereby confirming the probiotic properties of B. velezensis K12. B. velezensis K12 exhibits broad-spectrum bacteriostatic activity and in vitro safety, positioning it as a potential candidate strain for developing probiotic Bacillus preparations.